KAT6A, a Chromatin Modifier from the 8p11-p12 Amplicon is a Candidate Oncogene in Luminal Breast Cancer - Brittany Turner-Ivey; Stephen T. Guest; Jonathan C. Irish; Christiana S. Kappler; Elizabeth Garrett–Mayer; Robert C. Wilson; Stephen P. Ethier (2014)
The chromosome 8p11-p12 amplicon is present in 12% to 15% of breast cancers, resulting in an increase in copy number and expression of several chromatin modifiers in these tumors, including KAT6A. Previous analyses in SUM-52 breast cancer cells showed amplification and overexpression of KAT6A, and subsequent RNAi screening identified KAT6A as a potential driving oncogene. KAT6A is a histone acetyltransferase previously identified as a fusion partner with CREB binding protein in acute myeloid leukemia. Knockdown of KAT6A in SUM-52 cells, a luminal breast cancer cell line harboring the amplicon, resulted in reduced growth rate compared to non-silencing controls and profound loss of clonogenic capacity both in mono-layer and in soft agar. The normal cell line MCF10A, however, did not exhibit slower growth with knockdown of KAT6A. SUM-52 cells with KAT6A knockdown formed fewer mammospheres in culture compared to controls, suggesting a possible role for KAT6A in self-renewal. Previous data from our laboratory identified FGFR2 as a driving oncogene in SUM-52 cells. The colony forming efficiency of SUM-52 KAT6A knockdown cells in the presence of FGFR inhibition was significantly reduced compared to cells with KAT6A knockdown only. These data suggest that KAT6A may be a novel oncogene in breast cancers bearing the 8p11-p12 amplicon. While there are other putative oncogenes in the amplicon, the identification of KAT6A as a driving oncogene suggests that chromatin-modifying enzymes are a key class of oncogenes in these cancers, and play an important role in the selection of this amplicon in luminal B breast cancers.